Construction of Begomovirus AV1 Gene Candidate into pBI121 and Its Introduction into Tobacco by using Agrobacterium tumefaciens Vector - Santoso, Tri J.; Herman, Muhammad; Hidayat, Sri H.; Aswidinnoor, Hajrial; ., Sudarsono (Jurnal AgroBiogen, 2011)
Infection of Begomovirus has caused leaf curl disease in tomato. This infection has significantly impact on yield losses of tomato production. Recently, in Indonesia there was no effectively way to control this disease.  The use of resistant tomato variety is one of strategies to control this virus. Genetic engineering technology gives an opportunity to develop the transgenic tomato resistant to Begomovirus through pathogen derived resistance (PDR) approach. The objectives of this study were to construct the  Begomovirus AV1 candidate gene in the pBI121 and to introduce the construct into tobacco plant genome through Agrobacterium tumefaciens vector. A series activites in gene construct have been conducted include PCR amplification of AV1 gene using a pair of specific primer, cloning the gene into pGEM-T easy, transformation of the clone into Escherichia coli DH5α competent cell, construct the gene into pBI121, and transform the construct into A. tumefaciens. Leaf segments of in vitro tobacco plant were transformed by co-cultivation with A. tumefaciens containing ToLCV-AV1 construct. In the research activitiy, Indonesian  Begomovirus  AV1 gene  was  successfully amplified and inserted in expression vector plasmid pBI121. Tobacco transformants carrying kanamycin-resistant gene (nptII gene) were regenerated and established in the glasshouse. Those transformant plants are expected containing the AV1 gene.